Chronic recurrent multifocal osteomyelitis: State of the art - Gallego Eusse, Hernán Darío; Velásquez Franco, Carlos Jaime; Mesa Navas, Miguel Antonio (Medicina UPB, 2016)
Chronic recurrent multifocal osteomyelitis is a sterile autoinflammatory disease characterized by foci of sterile inflammation in the bone that generate recurrent pain. It is a rare entity in which the cardinal clinical manifestation is the presence of inflammatory bone lesions in metaepiphyseal regions of long bones, predominating in lower limbs. The disease is often associated with systemic symptoms and skin involvement making it part of the arthritis-dermatitis syndrome. The most common radiographic finding is osteolysis surrounded by a thin sclerotic halo, without periosteal reaction associated with bone formation or bone sequestrum. Magnetic resonance imaging allows early detection and facilitates the differential diagnosis between osteomyelitis and infections or bone tumors. Treatment is supported mainly by case reports and series of patients and consists of the use of nonsteroidal anti-inflammatory drugs and the use of bisphosphonates or tumor necrosis factor alpha antagonists in refractory cases. The prognosis of this disease is generally good, with a benign and self-limited clinical course in most cases.